TRADISI KAWIN TANGKAP DI SUMBA NTT PERSPEKTIF FILSAFAT MORAL EMMANUEL KANT - Laurensius Bembot; Donatus Sermada (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2022)
This research discusses the tradition of catching marriage (Piti Rambang) which is one of the marriage traditions of the Sumba people, East Nusa Tenggara. This tradition is the proposal of a girl by a man based on the agreement of the families of both parties. However, lately, the tradition of captive marriage has caused a polemic in the community, because it contains elements of violence in the form of coercion. Women are threatened by men who feel entitled to have a woman's personality even with violence. The purpose of this research is to examine the concept of human dignity in the tradition of captive marriage in Sumba, East Nusa Tenggara. Mentenghaui any factors that can violate human dignity, especially women. The author uses a qualitative method with a critical analysis approach from the perspective of Emmanuel Kant's moral philosophy, which sees that human dignity is the basis of moral principles. From this research it was found that the view of women in the tradition of captive marriage can demean and humiliate women's dignity. He is not free and his presence is often not as a person but as a commodity that can be traded.